Human dignity as heterotopia of criminal law (on the 100th anniversary of birth of professor I. I. Gorelik - Kharytonova, Olena V. (Journal of the Belarusian State University. Law, 2021)
This article is an attempt to comprehend the philosophical concept of heterotopia in the criminal law, filling it with content through the use of the concept of human dignity. Presenting human dignity as a special moving space for the formation of new meanings, determining the essential features of criminal law, the author offers an analysis of theoretical reflections and practical approaches in this area, highlighting the main planes in which their most prominent embodiment is carried out. While reviewing jurisprudence using the concept of human dignity in various jurisdictions, both national and international, the researcher emphasises the importance of both universal and contextual understanding of human dignity, its flexibility and ability to influence the development of current discourse on human rights. The rootedness of ideas about personal autonomy in human dignity, the prohibition of instrumentalisation and objectification of a person, the importance of the subjective status of the individual and the development of general humanity seem to be the main areas in which modern criminal law draws value meanings.
Keywords: human dignity; heterotopia; criminal law